Analisis Persediaan Bahan Kimia Karl Fisher Solvent Pada PT. XYZ dengan Metode Economic Order Quantity (EOQ) dan Periodic Order Quantity (POQ) - Ridho Kurniawan; Elly Ismiyah (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. XYZ is the most complete fertilizer producer in Indonesia, where every production process requires quality control and product quality assurance. In this case, a laboratory is needed to analyze the quality of the products produced. One of the supporting materials in product quality analysis, namely liquid chemicals, is Karl Fisher Solvent. This research was conducted to calculate and analyze the comparison of order quantity, order frequency, safety stock, reorder point, and total inventory costs using 2 inventory control methods EOQ and POQ, so that it can be seen which method is the most optimal. , EOQ, POQ, or company. The analysis results show that the most optimal method for inventory control, namely the EOQ method, can save inventory costs by 22% with an order quantity of 39 liters, order frequency 4 times, total inventory costs of Rp. 284,771, safety stock 4 liters and reorder point 10 liters.